Corporate digital responsibility (CDR) in Germany: background and first empirical evidence from DAX 30 companies in 2020 - Ute Merbecks (Journal of Business Economics, 2023)
Corporate digital responsibility (CDR) is a recently developing new management concept in response to the increasing challenges caused by digital transformation. In Germany, this self-governance approach influenced the political discussions and led to a more integrative and collaborative multi-policy strategy beyond pure regulatory regimes. The launch of the German CDR-code by the German action group in June 2021 is a milestone to capture ethical problems in digitalised firms by voluntary commitments from signatories. However, little empirical evidence on the current state of CDR-initiatives at German corporations is available up-to now. This article addresses the identified research gap by performing a qualitative analysis of the disclosed information on CDR in nonfinancial reports of the DAX~30 companies from 2020. After a brief introduction, a literature review on CDR-related research activities is presented in Sect.~2, and the context and background of the study are specified. Section~3 presents the results of the empirical study on disclosed CDR-related information by German DAX 30 companies. Section~4 concludes with a discussion and discovers future research avenues on CDR. Corporate responsibility in the digital economy is a field of research that is open for different disciplines and especially theoretical normative research on CDR should be accelerated.
Keywords: M48; M14; G30; 650; Digitalisation; Sustainability reporting; Corporate responsibility; Business ethics